2020
DOI: 10.1002/eqe.3355
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the reduction factors of seismic capacity for damaged RC column members using the experiment database

Abstract: Static‐cyclic loading is used to identify the reduction factors of seismic capacity of damaged reinforced concrete (RC) column members. The reduction factors of seismic capacity that are obtained from specimens damaged under static‐cyclic loading differ from those obtained in dynamic testing, and this difference is investigated in this work. The experimental results obtained in this work, previously obtained results, and the “Pacific Earthquake Engineering Research Center Structural Performance Database (PEER)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Chiu et al 13 . proposed the reduction factor values for RC columns by using the identical damage states as defined in the JBDPA guideline.…”
Section: Framework For Vision‐based Postearthquake Residual Capacity ...mentioning
confidence: 99%
See 3 more Smart Citations
“…Chiu et al 13 . proposed the reduction factor values for RC columns by using the identical damage states as defined in the JBDPA guideline.…”
Section: Framework For Vision‐based Postearthquake Residual Capacity ...mentioning
confidence: 99%
“…The development of visible damage is suspected to be related to the loading history and loading rate 26 . Experiments by Chiu et al 13 . indicated that quasi‐static loading resulted in significantly wider cracks than dynamic loading at identical deformation amplitudes.…”
Section: Postearthquake Performance Assessment Of the Shaking Table T...mentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis of damage degree in reinforced concrete (RC) buildings under seismic vibration is of the highest priority, which can provide the data support for post-disaster reconstruction. 1,2 For example, accurate measurement of deformed RC structures can be assessed according to the measured angle of inter-story drift, which is directly related to the level of damage. 3,4 However, there are many RC structures that were built just 10 years ago, few of these structures have embedded sensors.…”
Section: Introductionmentioning
confidence: 99%